Making Room for Renters : Understanding and Supporting Rental Markets in the Global South — Evidence from Dar es Salaam, Tanzania - Panman, Alexandra; Lozano Gracia, Nancy (World Bank, Washington, DC, 2021)
Many people in the global south access housing through informal rental markets, but remarkably little is known about how these markets work or the quality of the accommodations on offer. This paper draws on a unique new data set to analyze the informal rental market in a case study city: Dar es Salaam, Tanzania. The picture that emerges is one of a large, anonymous market in which there are clear price premiums for accommodation and neighborhood quality. At the same time, however, demand for quality housing outstrips supply, confining even upper-income households to slum conditions. The findings shed light on market dynamics that shape access to adequate housing in Dar es Salaam and other cities across the world. The paper closes by drawing on these insights to make recommendations to improve existing urban development policies such as slum upgrading, as well as to develop new approaches to rental housing that can materially improve living conditions in the rapidly expanding cities of the Global South.